(untitled) (Experimental biology, 2018)
Relevance of studying of Rumex L. species from Kazakhstan, on the base of analysis of complex phytopreparations and individual substances of Rumex L. plants, given on biological activity, has been shown. Prospects of use of Rumex tianschanicus A. Los. as raw materials for preparation of polyphenolic phytopreparations, have been proved. Comparative results of the quantitative phytochemical and qualitative component analysis of anthocyanin, anthraquinone, coumarin and flavonoid metabolites in leaves, stalks and the roots of Rumex tianschanicus A. Los., have been presented. Features of dynamics of accumulation of biologically active substances, depending on vegatation phase of plant, have been revealed. Modified methodology of extraction of polyphenolic metabolites of Rumex tianschanicus A. Los., has been represented. HPLC preparative separation and analytical determination of individual substances of Rumex tianschanicus A. Los., with use of authentic samples, has been carried out. Activity against Staphylococcus aureus, Bacillus subtilis gram-positive bacteria, Pseudomonas aeruginosa, Escherichia coli gram-negative bacteria and a Candida albicans fungal yeast, for 3 extracted anthocyanins, 6 – anthraquinones, 4 – coumarins, - 7 - flavonoids, was investigated. Substances which have shown the activity, exceeding antibacterial effect of gentamycin and sodium salt of benzylpenicillin, and also antifungal effect of nystatin have been revealed.